Life of Autism: Short Movie - Ahmad Dhiauddin Kamarudin; Myzan Binti Noor (Journal of Computing Technologies and Creative Content, 2022)
Even in the modern society, there are people who don’t recognise or have never heard of autism before. There may be people who have knew of the word but do not encounter it. In this society, autism is often regard as a disease. Factually, it is rather a developmental disorder. Mostly, people understood that when a child learns to speak at a later age, they are deemed as ‘autistic’. Such a notion is inaccurate because he or she is not necessarily autistic. In addition, some people do not understand the emotions of children with autism. Things as such are what causes people to ignore about autism and conclude tha it’s just the children’s problem. The problem statement here is that the community lacks the knowledge and the experience with an autistic, therefore the community does not know the symptoms of autism and how to cope with them. The objective of this study was to introduce autism disorders to the community and how to overcome it as a problem. Both of these objectives were chosen because they relate to the researcher’s project. The used method used was to create animated cartoons and share them on a platform such as YouTube to convey the message to the general public. In conclusion, the researcher proposed to make an animated cartoon with the theme “autism”, to convey a message to the about the awareness.